Evaluation of the relationship between non-alcoholic fatty liver disease and serum c-peptide, c-peptide to glucose and c-peptide to HbA1C ratio in obese children - Demirbaş, Fatma; Dinler Çaltepe, Gönül; Comba, Atakan; Abbasguliyev, Hasan; Kalaycı, Ayhan Gazi (Journal of Surgery and Medicine, 2020)
Aim: Obesity-related complications such as metabolic syndrome, insulin resistance and non-alcoholic fatty liver disease (NAFLD) have increased in childhood. The aim of this study is to investigate the fasting c-peptide, c-peptide to glucose and c-peptide to HbA1C ratios in obese children with NAFLD. Methods: This case-control study was conducted from August through November 2018. A total of 60 obese children, 40 with and 20 without NAFLD, were included in the study. Patients with BMI > 2 z-score were considered obese. The ultrasonographic characteristics of NAFLD were identified with liver contrast and brightness in echogenicity. Serum fasting c-peptide levels of patients were compared. Results: Of the 60 patients included in the study, 37 (61.7%) were male and the mean age was 11.9 (2.9) years. The mean ALT, weight BMI, waist circumference, waist to height ratio, serum c-peptide, fasting c-peptide to glucose ratio, fasting c-peptide to HbA1C ratio and insulin levels were considerably higher in patients with NAFLD (P<0.05 for each). When the c-peptide levels of all the patients was evaluated by ROC analysis, the area under the curve in patients with NAFLD was 0.70 (95% CL: 0.725-0.955) and the c-peptide cut off value was 2.62 ng/ml (sensitivity 60%, specificity 75%, P=0.011). Logistic regression analysis results showed that the risk of NAFLD was significantly higher in obese children with c-peptide levels greater than 2.62 ng/ml (OR: 4.52 95% CI: 1.65-3.25) (P<0.001). Conclusion: In our study, a significant relationship was found between NAFLD and serum c-peptide level, c-peptide to glucose and c-peptide to HbA1C ratios. Even though BMI, waist circumference, waist to height ratio, HbA1c and insulin are better parameters in determining insulin resistance in NAFLD patients, c-peptide can be used as an inexpensive method for screening.